The Semiotic dimension in the production of sports media legends - أحمد هادي عبد الله (ALBAHITH ALALAMI, 2016)
Sports and legend rooted deep in human history, and although they meet in the oldest epics as was the hero Gilgamesh legend and a hero of the heroes of wrestling has been named the oldest regular sports tournament in history in his name, a Algeljamchih Games which will be held events in Mesopotamia in August of each year and will continue nine days and take place in competitions in more than a sports game .. In our time re-production of sports legends to serve the objectives of the huge investment both sports on the commercialization level or at other levels of marketing, including political marketing. In this context, a move sports media for the production of myths we studied Semiaiaa in an effort to learn how the production process for sports legend today and our aim to clarify the process mechanisms or industry to Oalamyina as well unraveled publicly supervisor sporting events, which serve in the field of media education. The historical approach we have followed in the asset tracking and Roland Barthes’s approach in the detection of semiotic dimension to produce legends today, which found that it produced in the two circles, the first outside the sports center and the second inside the sports center and to rub shoulders among other objectives, seeks to achieve sporting legend.